Estimating the counterparty risk exposure by using the Brownian motion local time - Bonollo, Michele; Di Persio, Luca; Mammi, Luca; Oliva, Immacolata (Zielona Góra: Uniwersytet Zielonogórski)
In recent years, the counterparty credit risk measure, namely the default risk in over-the-counter (OTC) derivatives contracts, has received great attention by banking regulators, specifically within the frameworks of Basel II and Basel III. More explicitly, to obtain the related risk figures, one is first obliged to compute intermediate output functionals related to the mark-to-market position at a given time no exceeding a positive and finite time horizon. The latter implies an enormous amount of computational effort is needed, with related highly time consuming procedures to be carried out, turning out into significant costs. To overcome the latter issue, we propose a smart exploitation of the properties of the (local) time spent by the Brownian motion close to a given value.
Keywords: counterparty credit risk; exposure at default; local times Brownian motion; over-the-counter derivatives; Basel financial framework